2010
DOI: 10.1073/pnas.0910106107
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of appropriately evaluated safe-induced pluripotent stem cells for spinal cord injury

Abstract: Various types of induced pluripotent stem (iPS) cells have been established by different methods, and each type exhibits different biological properties. Before iPS cell-based clinical applications can be initiated, detailed evaluations of the cells, including their differentiation potentials and tumorigenic activities in different contexts, should be investigated to establish their safety and effectiveness for cell transplantation therapies. Here we show the directed neural differentiation of murine iPS cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
405
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 480 publications
(418 citation statements)
references
References 50 publications
3
405
3
3
Order By: Relevance
“…Next, we used a mouse iPS cell clone whose safety had been confirmed (38 C2 clone), to study the effectiveness of treating SCI by transplanting neurospheres derived from it into the lesion site in a mouse model [31]. The 38 C2-iPS-derived secondary neurosphere (38 C2-SNS) transplantation was performed in the subacute stage on day 9 after the injury.…”
Section: Transplantation Of "Safe" Mouse Ips Cell-clone-derived Neuramentioning
confidence: 99%
“…Next, we used a mouse iPS cell clone whose safety had been confirmed (38 C2 clone), to study the effectiveness of treating SCI by transplanting neurospheres derived from it into the lesion site in a mouse model [31]. The 38 C2-iPS-derived secondary neurosphere (38 C2-SNS) transplantation was performed in the subacute stage on day 9 after the injury.…”
Section: Transplantation Of "Safe" Mouse Ips Cell-clone-derived Neuramentioning
confidence: 99%
“…Although the use of ES cells dictates an allogeneic donor cell source, the recent generation of induced pluripotential stem (iPS) cells from somatic mouse [213] cells and from human [214,215] [216][217][218] and oligodendrocytes [219,220]. It will now be necessary to explore the potential for generating populations of iPS-derived oligodendrocytes for autologous grafting in the myelin disorders.…”
Section: Embryonic Stem and Induced Pluripotential Cellsmentioning
confidence: 99%
“…Another safety concern is related to the sustained proliferation of implanted cells. To address this, a protocol to evaluate non-tumor forming "safe" iPSC lines was developed for therapeutic applications [10,11]. When this screening process is used, iPSCs show a lower risk of tumour formation compared to otherwise unscreened ESCs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the somatic cell type from which iPSCs are derived and choice of reprogramming factors affect the ability of the cells to differentiate into desired types [14]. However, despite the comparatively lower efficiency, these studies have shown successful differentiation of iPSCs into neural phenotypes including, neurons, astrocytes, and oligodendrocytes [11][12][13][14]. Thus, progress toward more efficient neural differentiation protocols represents an important step in the development of clinically relevant iPSC-based regenerative therapies for the diseases and disorders of the nervous system [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation